Does off-pump coronary revascularization reduce mortality in re-operative coronary artery surgery? A meta-analysis of observational studies. (July 2013) - Sepehripour, AH; Saso, S; Harling, L; Punjabi, P; Ashrafian, H; Athanasiou, T
Background: Re-operative coronary artery bypass grafting (CABG) is a challenging operation that is often performed in a high-risk patient group. Avoiding cardiopulmonary bypass (CPB) in these patients is hypothesised to be advantageous due to the reduced invasiveness and physiological stress of off-pump coronary artery bypass grafting (OPCAB). The aims of this study were to assess whether OPCAB may improve outcomes in patients undergoing re-operative CABG. Methods: Twelve studies, incorporating 3471 patients, were identified by systematic literature review. These were meta-analysed using random-effects modelling. Primary endpoints were 30-day and mid-term mortality. Secondary endpoints were completeness of revascularization, mean number of grafts per patient and the effect of intra-operative conversion on mortality. Results: A significantly lower rate of 30-day mortality was observed with OPCAB (OR 0.51, 95% CI [0.35, 0.74]), however, no difference was demonstrated in mid-term mortality. Significantly less complete revascularization and mean number of grafts per patient were observed in the OPCAB group. Meta-regression revealed no change in 30-day mortality when the effect of conversion from one technique to the other was assessed. Conclusions: Off-pump techniques may reduce early mortality in selected patients undergoing re-operative CABG; however, this does not persist into mid-term follow-up. OPCAB may also lead to intra-operative conversion and, although this did not affect outcomes in this study, these results are constrained by the limited data available. Furthermore, OPCAB may increase target vessel revascularization and, consequently, incomplete revascularization which, whilst not reflected in the short-term outcomes, requires longer-term follow-up in order to be fully assessed.